Pengukuran Beban Kerja Mental pada Karyawan Quality Control di PT Delta Dunia Tekstil 1 dengan Menggunakan Metode Nasa-Tlx - Aqsal Faiz Al Hayy; Anita Oktaviana Trisna Devi; Erna Indriastiningsih (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Work fatigue is a significant issue faced by employees in Indonesia, with approximately 65% experiencing symptoms that reduce their concentration and performance. Excessive workload, particularly mental workload, can result in cognitive strain and decreased productivity. This study aims to measure the level of mental workload experienced by quality control employees at PT Delta Dunia Tekstil I using the NASA Task Load Index (NASA-TLX) method. The research also investigates the relationship between employees’ age, length of service, and perceived mental workload through T-tests and F-tests to provide a more comprehensive analysis. Data were collected from 20 quality control employees who are responsible for monitoring textile production under strict standards. Results from NASA-TLX calculations indicate that the average mental workload falls within the high category, with effort and own performance emerging as the dominant dimensions contributing to mental strain. Correlation analysis shows a negative but not statistically significant relationship between age, length of service, and mental workload, suggesting that other factors play a stronger role in shaping employees’ perceptions. The study further highlights fluctuations in employee attendance and quality performance indicators, emphasizing the importance of workload evaluation. To address these issues, recommendations include adding more operators per machine, which is projected to reduce mental workload scores by approximately 33%. Such measures can optimize task distribution, improve efficiency, and promote employee well-being. Overall, the findings suggest that systematic workload assessments using tools such as NASA-TLX are essential for enhancing productivity and supporting sustainable human resource management in the textile industry.